Surgical management of critical femoral bone loss by bone transport over intramedullary nail by monorail system: a case report - Nahar, Kuldeep; Nahar, Nikita (International Journal of Research in Orthopaedics, 2020)
Present case report is about a male patient who met with a road traffic accident sustained an open crush, contaminated, injury of lower end femur of right side with significant loss of lower thigh bone (8 cm). He had fracture of inter condylar femur with fracture upper end tibia and lower third tibia with impending vascular insufficiency of leg and foot. Operated after correction of anaemia by debridement, fixation of femur with plate and inter condylar screw. Upper end tibia and Lower half tibia were fixed with separate plates and fasciotomy of leg. After 2 months femoral plate was replaced with intramedullary locking nail and superadded with monorail fixator. Corticotomy at proximal femur for bone transportation. Bone gap was corrected within 4 months and bone grafting was done at distal docking site. Union achieved and fixator removed after 4 months of this. Patient showed good results till last follow up 28 months, having good range of motion of knee.so critical bone loss at femur was treated by distraction osteogenesis over intramedullary nail with monorail external fixator system.